Timing of delivery of malaria preventive interventions in pregnancy: results from the Tanzania national voucher programme. Issue 1 (5th November 2009) - Marchant, Tanya; Hanson, Kara; Nathan, Rose; Mponda, Hadji; Bruce, Jane; Jones, Caroline; Sedekia, Yovitha; Mshinda, Hassan; Schellenberg, Joanna
Abstract : Background: Across sub-Saharan Africa, pregnant women attend routine health services around the 20th week of gestation. Objective: To investigate, with a view to maximising effectiveness of malaria control tools delivered via routine services, coverage of an antenatal clinic insecticide-treated net (ITN) voucher scheme in Tanzania by gestational age. Methods: Household and antenatal clinic survey data from 21 districts in Tanzania were collected and analysed annually 2005–2007. Optimal voucher protection was defined as giving women access to vouchers for 24 weeks of pregnancy (weeks 16 and 40 gestation). The relationship between gestational age and use of ITNs throughout pregnancy was explored. Results: Coverage of the ITN voucher was high (84% in 2007), but only 61% of optimal voucher protection was achieved. It was reduced by a combination of late attendance at clinic and staff not distributing vouchers at first visit. An increasing trend by gestational age in ITN use was observed each survey year, rising in 2007 from 23% of first-trimester women to 30% of women post partum (χ 2 =5.9, p=0.01). Conclusion: Uptake of malaria interventions is not evenly distributed throughout pregnancy. Including gestational age in pregnancy coverage indicators can enhance understanding of the public health potential available from pregnancy interventions.